Antimutagenicity of arugula(Eruca sativa) and carrot (Baghdad Science Journal, 2005)
Been studying the opposite effect of mutagenesis to juice plant watercress and compared juice carrots to induce mutations resistant Struptomaysan Palmtafr (NTG) and transactions as diverse as the use of juice before treatment Palmtafr or after using Almtafr or with Almtafr using system mutagenesis Bactra consisting of three isolates G3, G12, G27 are very sensitive to Struptomaysanstudy resulted in a user juice plants had no effect on the neighborhood number of isolates, but its effect on the watercress was clear